A New Approach to the Synthesis of Acyclic Nucleotide Phosphonate Analogues with Triple or Double Bonds - Brel, Valery K. (Synthesis, 2012)
On the basis of new methodology to design the phosphonate analogues of nucleotides, the first series of acyclic nucleotides possessing a triple bond in the carbon skeleton were prepared by coupling diethyl 4-chlorobuta-1,2-dienylphosphonate with the corresponding purine or pyrimidine nucleic bases under base-catalyzed alkylation conditions.
Keywords: allenes; alkylation; antiviral agents; DNA; heterocycles; hydrogenation; nucleotides; phosphorus